2020
DOI: 10.1186/s12885-020-06755-y
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and PD-L2 expression in the tumor microenvironment including peritumoral tissue in primary central nervous system lymphoma

Abstract: Background: The prevalence of programmed death-ligand 1 (PD-L1) and PD-L2 expression on tumor cells and tumor-infiltrating immune cells in primary central nervous system lymphoma (PCNSL) remains unclear. In the present study, we analyzed needle biopsy and craniotomy specimens of patients with PCNSL to compare the PD-L1 and PD-L2 levels in the tumor and surrounding (peritumoral) tissue. We also assessed the correlation between biological factors and the prognostic significance of PD-L1 and PD-L2 expression. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Various studies have investigated the PD-L1 expression in the PCNSL microenvironment. According to past reports, the expression of PD-L1 is more frequently detected on tumor infiltrating cells, including macrophages than tumor cells 10 , 13 , 15 17 . Our results show similar trends.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Various studies have investigated the PD-L1 expression in the PCNSL microenvironment. According to past reports, the expression of PD-L1 is more frequently detected on tumor infiltrating cells, including macrophages than tumor cells 10 , 13 , 15 17 . Our results show similar trends.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the association between PD-L1 and survival in patients with PCNSL, the past literature showed that the PD-L1 expression in tumor cells was correlated with overall survival and that the median survival time was not reached among patients with PD-L1-positive tumor cells and 31.7 months among those with PD-L1-negative tumor cells, although the PD-L1 expression in tumor stromal cells was not correlated with overall survival 10 . On the other hand, Furuse et al analyzed the expression of PD-L1 and PD-L2 in both tumor and peritumoral tissues and revealed that PD-L1-positivity of intratumoral and peritumoral macrophages predicted a favorable outcome 13 . Our results showed that tumor cell PD-L1 positivity was associated with longer overall survival in comparison to PD-L1 negativity; however, this factor was excluded by a multivariate Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, PD-L2 is also expressed on tumor cells and involved in antitumor immune suppression (Latchman et al, 2001;Taube et al, 2014;Yearley et al, 2017;Larsen et al, 2019;Liao et al, 2019;Tanegashima et al, 2019;Nakayama et al, 2020). Moreover, PD-L2 not only possesses higher affinity for PD-1 than PD-L1 does but also may be highly coexpressed with PD-L1 in tumor cells and tissues (Youngnak et al, 2003;Cheng et al, 2013;Morales-Betanzos et al, 2017;Tang and Kim, 2019;Furuse et al, 2020;Wolkow et al, 2020). It is worth mentioning that proteolytic degradation or alternative splice variants also produce soluble PD-L2, which may be a complementary biomarker (He et al, 2004;Dai et al, 2014;Fukasawa et al, 2017;Costantini et al, 2018;Buderath et al, 2019;.…”
Section: Exopd-l1 As a Biomarker For Efficacy Of Anti-pd-1/pd-l1 Therapymentioning
confidence: 99%